2021
DOI: 10.3846/ijspm.2021.14914
|View full text |Cite
|
Sign up to set email alerts
|

Consumption and Investment Values in Housing Price: A Real Options Approach

Abstract: Homeowners can be viewed as the put option holders who can sell housing to lenders when the housing price is lower than its mortgage value and sell houses when the housing price rises above a certain threshold. On the basis of the theory of investment under uncertainty, we model the housing value from the perspective of houseowners who can choose to either live in their houses or switch houses for comfort improvement and price appreciation. We can decompose the housing value into consumption and investment val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Works by Henderson (1987), Arrondela and Lefebvreb (2001) and Cassidy et al (2008) have analysed the choice of tenure by separating the demand for housing into service/consumption demand and investment demand. The dual role of housing results in its heterogeneity and thus raises the volatility of price and possibility of overheating in housing market (Hung and Tzang, 2021). In addition to this, it was found that when individuals have more capital in hand, there exists speculative intent in real estate purchase decisions, which consequently results in structural changes in real estate prices.…”
Section: Literature Review Construction Industry Output Demand Stimul...mentioning
confidence: 99%
“…Works by Henderson (1987), Arrondela and Lefebvreb (2001) and Cassidy et al (2008) have analysed the choice of tenure by separating the demand for housing into service/consumption demand and investment demand. The dual role of housing results in its heterogeneity and thus raises the volatility of price and possibility of overheating in housing market (Hung and Tzang, 2021). In addition to this, it was found that when individuals have more capital in hand, there exists speculative intent in real estate purchase decisions, which consequently results in structural changes in real estate prices.…”
Section: Literature Review Construction Industry Output Demand Stimul...mentioning
confidence: 99%
“…In this study, we extend the model of Hung and Tzang (2021) to derive the value of high-end housing premiums and obtain an analytical solution to the luxury value. To the best of our knowledge, our model is the first to theoretically evaluate high-end housing premiums.…”
Section: Introductionmentioning
confidence: 99%
“…Here w H is the same as w denoted inHung and Tzang (2021).9 The rental utility can be estimated according toCampbell and Cocco (2015)'s model. As it is not the main concern of this study, we assume that w j is an exogenously set variable.…”
mentioning
confidence: 99%